1999
DOI: 10.1177/073346489901800105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resident and Facility Risk Factors for Psychotropic Drug Use in Nursing Homes Since the Nursing Home Reform Act

Abstract: The purposes of this article are to identify resident and facility risk factors for the use of psychotropic drugs since the implementation of the Nursing Home Reform Act (NHRA) and to compare these results with resident and facility risk factors prior to the implementation of the NHRA. The results update our knowledge of resident risk factors for psychotropic drug use and identify important but previously unexplored facility risk factors for their use. No evidence was found that particular types of nursing hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Over the last few years, studies from the US and Scandinavia have shown a reduction in antipsychotic drug use among institutionalized patients (12,13,23,24). A few studies however (28,29), describe increased use of antipsychotics in NHs during the last decade.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Over the last few years, studies from the US and Scandinavia have shown a reduction in antipsychotic drug use among institutionalized patients (12,13,23,24). A few studies however (28,29), describe increased use of antipsychotics in NHs during the last decade.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Despite the importance and potential impact of the HCFA guidelines, few studies have analyzed BZ use before and after the guidelines were implemented in 1992. Castle 14 found no change in levels of anxiolytic/hypnotic drug use before and after HCFA guidelines were implemented but did not evaluate compliance with HCFA guidelines or patterns of BZ use. Groce et al 15 examined compliance with anxiolytic/hypnotic guidelines by 74 older persons in four facilities targeted by pharmacists for special audits, inservices, and other interventions.…”
mentioning
confidence: 97%
“…The second goal was to analyze the effects of resident mix, nurse staffing, and other facility characteristics on BZ prescribing and chronic use after guideline implementation. Based on past studies of psychoactive drug use in nursing homes, we hypothesized that postimplementation rates of BZ prescribing and chronic use would be higher in facilities with greater psychiatric morbidity 14–16 and poorer nurse staffing 17–20 . The literature is less clear about the effects of resident demographic mix and other facility characteristics such as size, for‐profit ownership, and Medicaid reimbursement rates.…”
mentioning
confidence: 99%
“…Studies of drug use from 1986 to 1993 have found significant declines in the use of antipsychotic drugs but no change in the use of anxiolytics and hypnotics (5,13,19,26,31). However, we believe the results are relevant, for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…We also hypothesized that residents who demanded medication would have higher rates of as-needed drug use and of chronic use (23,24). Our control variables included age, gender, whether dementia was present, whether behavioral problems were present, payment source, and number of prescribed benzodiazepines (19,(26)(27)(28).…”
mentioning
confidence: 99%